A systematic Study of Security Challenges and Infrastructures for Internet of Things - Koteswara Rao, N.; Swain, Gandharba (International Journal of Engineering and Technology, 2018)
The proliferation of smart objects with capability of sensing, processing and communication has grown in recent years. In this scenario, the Internet of Things (IoT) connects these objects to the Internet and provides communication with users and devices. IoT enables a huge amount of new applications, with which academics and industries can benefit, such as smart cities, health care and automation. In this environment, compose of constrained devices, the widespread adoption of this paradigm depends of security requirements like secure communication between devices, privacy and anonymity of its users. This paper presents the main security challenges and solutions to provide authentication and authorization on the Internet of Things.Â
Keywords: .